Burden of Vitamin D Deficiency and its Related Risk Factors in Early Pregnancy - Zahra Wasim, Faiqa Chughtai, Sana Yousaf, Tahira Riaz, Tabassum Muzaffar, Adiba Akhtar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the burden of Vitamin D deficiency and its related risk factors in early pregnancy. Study Design: A cross-sectional study. Place and Duration of the Study: The Department of Obstetrics & Gynecology, The Combined Military Hospital (CMH), Risalpur, Pakistan from 1st January 2021 to 31st December 2021. Methodology: A total of 370 healthy pregnant women visiting outpatient department in the 1st trimester for routine pregnancy examination and willing to be part of this study were included. Vitamin D deficiency was labeled as serum 25(OH)D <20 ng/mL, insufficiency as 20-32 ng/mL and sufficiency >32 ng/mL. Demographic and anthropometric characteristics along with socio-economic status, clinical profile, supplementary intake and details of life style and daily living patterns were noted in all women. Results: In a total of 370 pregnant women, mean age was 29.92±5.5 years. Multivariate binary logistic regression analysis showing association of vitamin D insufficiency/insufficiency with daily sunlight exposure below 1 hour (p<0.001), low socioeconomic status (p=0.002), working women (p=0.025), no use of vitamin D supplementation before pregnancy (p=0.044) and no use of vitamin D in the current pregnancy (p=0.001). Conclusion: Serum vitamin D levels of majority of the pregnant ladies in the 1st trimester were found to be either deficient or insufficient. Less daily sunlight exposure, low socioeconomic status, working women, no use of vitamin D supplementation before pregnancy or during 1st trimester were found to have significant association with vitamin D deficiency.